DOES CRYOPRESERVATION TECHNOLOGY HELPS TO FORENSIC MEDICINE AND TISSUE ENGINEERING? (Journal of Forensic Medicine & Toxicology, 2015)
Background: Cryopreservation has been found efficacious for thin samples, small clumps of cells, which can be cooled more quickly, hence requiring lower doses of toxic cryoprotectants. The goal of cryopreserving human livers, hearts, and other body organs for storage and transplantation is still some distance away. Methods: An appropriate combination of cryoprotectants and regimes of rapid cooling and rinsing during warming often allows successful cryopreservation of biological materials, particularly cell suspensions or thin tissue samples. Examples include: Semen blood, tissue samples like tumors, histological cross sections, human eggs and human embryos. Many studies have evaluated the children born from frozen embryos, or “frosties”, with consistently positive results with no increase in birth defects or development abnormalitie). Results: Cryopreserver would have enormous applications, especially in combating infertility, anamenting trauma care, and in regeneration of tissue, organs in lab set up. Moreover, it is cost effective and feasible technique. Conclusions: Currently not much of work has been done to establish or optimize the techniques in the Indian setting. Future studies are therefore needed for standardizing the techniques of cryo so as to ensure optimum cell survival. We established and first time hypothesized globally that it helps tissue banking/ engineering and forensic medicine as well. We easily save so many lives in future.
Keywords: Cryopreservation; human oocytes; unfertilized oocytes; Stem cells; Autologous bone marrow; Transplant